(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1972)
A significant factor for antigens efficiency is the presence, in culture, of high S — bacteria percentages. Even though using innoculum with reduced S — bacteria concentration, the above conditions may be obtained through aeration of cultures in soldi media. The use of this antigens preparation technique is recommended for the final cultivation stage. It may be used by itself, however better results will be reached through its association with one of the methods described in literature, developed to obtain S or SR bacteria — free (or almost free) innoculum.